Tax Planning PPh Pasal 21 di Koperasi Karyawan Redrying Bojonegoro (KAREB) Sebagai Upaya Efisiensi Beban Pajak Perusahaan - Hermawan Budi Prasetiyo; Dina Alafi Hidayatin; Hendra Fatkhur Rohman (Universitas Trunojoyo Madura, 2019)
The purpose of this study is to provide recommendations on the calculation of Income Tax Article 21 in KAREB Cooperative by conducting Tax Planning using the Gross method and the Gross Up method. The study was conducted with a qualitative method, namely comparative descriptive. The research data are in the form of the recapitulation of employee salaries in 2018 and company's financial statements in 2018. In addition, researchers also conduct interviews and observations to provide a picture of the validity and accuracy of the data. Researchers also conduct literature studies to compile research results with pre-existing theories. The results found that the method of calculating Article 21 Income Tax which was the most efficient and could be recommended was the gross up method by providing tax allowance to employees.